2012
DOI: 10.4161/epi.22191
|View full text |Cite
|
Sign up to set email alerts
|

Novel target genes and a valid biomarker panel identified for cholangiocarcinoma

Abstract: Cholangiocarcinoma is notoriously difficult to diagnose, and the mortality rate is high due to late clinical presentation. CpG island promoter methylation is frequently seen in cancer development. In the present study, we aimed at identifying novel epigenetic biomarkers with the potential to improve the diagnostic accuracy of cholangiocarcinoma. Microarray data analyses of cholangiocarcinoma cell lines treated with epigenetic drugs and their untreated counterparts were compared with previously published gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 48 publications
2
90
0
1
Order By: Relevance
“…[49]. Andresen et al identified CDO1, DCLK1 and ZSCAN18 as novel frequently methylated biomarkers in CCA, and confirmed frequent methylation of SFRP1 [52]. These findings suggest that many signaling pathways can be involved in the development and progression of CCA and DNA methylation may be a potential source of diagnostic, prognostic and predictive biomarkers [49].…”
Section: Dna Methylation In Cholangiocarcinomamentioning
confidence: 75%
See 1 more Smart Citation
“…[49]. Andresen et al identified CDO1, DCLK1 and ZSCAN18 as novel frequently methylated biomarkers in CCA, and confirmed frequent methylation of SFRP1 [52]. These findings suggest that many signaling pathways can be involved in the development and progression of CCA and DNA methylation may be a potential source of diagnostic, prognostic and predictive biomarkers [49].…”
Section: Dna Methylation In Cholangiocarcinomamentioning
confidence: 75%
“…The methylation of a specific CpG site in the TTP promoter leads to its silencing and consequent Hypermethylation Trascriptional regulator [52] increased level of c-Myc, blocking the effect of TGF-␤1. DNMT3A seems to be the prominent responsible for the methylation of TTP promoter [45].…”
Section: Dna Methylation In Hepatocellular Carcinomamentioning
confidence: 99%
“…For example, the promoter of SOCS3, which is the upstream regulator of JAK/STAT cytokine signaling was frequently hypermethylated in CCA [35,39]. The Wnt signaling modulator, SFRP1 was also hypermethylated in CCA at frequencies as high as 85% [40]. On the other hand, hypermethylation of SFRP2 promoter leading to its lower M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 expression, was correlated with poor prognosis [41].…”
Section: Aberrant Epigenetic Landscapementioning
confidence: 93%
“…Bisulphite modified DNA samples were PCR-amplified using either an unmethylation-specific (CDO1U) or methylation-specific (CDO1M) primer pairs described before ( Fig. 2) (Andresen et al 2012). The methylation primer sense was 5′-TTGGGACGTCGGAGATAAC-3′ and antisense, 5′-GACCCT CGAAAAAAAA ACGA-3′.…”
Section: Methylation-specific Pcrmentioning
confidence: 99%